A novel approach for forming carbon nanorods on the surface of carbon felt electrode by catalytic etching for high-performance vanadium redox flow battery. (March 2018) - Abbas, Saleem; Lee, Hyuck; Hwang, Jinyeon; Mehmood, Asad; Shin, Hyun-Jin; Mehboob, Sheeraz; Lee, Ju-Young; Ha, Heung Yong
Abstract: In this work a novel method is unfolded to modify carbon felts (CF) to substantially improve the performance of the electrodes for vanadium redox flow batteries (VRFBs). The carbon felt, a well-known electrode material for VRFB, is catalytically etched by cobalt oxide to form carbon nanorods on the surface of the fibers comprising the CF. Unlike conventional multistep processes to grow nano-structures on carbon felts, this method simply involves a thermal treatment of catalyst-loaded felt in air to produce well aligned nanorods on its fibers. The surface morphology is optimized by etching temperature, treatment time and catalyst type. The catalytically etched CF shows an improved surface wettability and an enlarged specific surface area about two times compared to pristine CF that lead to an improvement of kinetics towards vanadium redox reactions. When used as electrode in all-vanadium redox flow battery, the nanorod-structured CF shows around 35% higher charge/discharge rate capability at 150 mA cm −2 and 80% retained-capacity compared to 48% in case of un-etched CF as confirmed by a long run test with a hundred cycles of charge/discharge operation at 50 mA cm −2 . Graphical abstract: Image 1